Nenglish: An Inevitable Reality or Merely a Mirage - Duwadi, Eak Prasad (Journal of NELTA, 2011)
Several discussions are being held on which variety of English to adopt and adapt to it around the world. Nepal, where modern English education began in the 1850s, is also at the crossroads because English teachers and practitioners here are in dilemmas whether to follow British/American versions, Hinglish (Indian variety of English) or their own Nenglish (Nepali Variety of English). Although there is a trend of developing local varieties around the world, some scholars are skeptic as this championing can lead to anarchy in a small developing country like Nepal. Key words: Nenglish; Hinglish; Received pronunciation; Standard English Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 43-53 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4608